PENGARUH UMPAN BALIK, KOORDINASI TERHADAP KEMAMPUAN OBJEK KONTROL SISWA PAUD - Syahrial Bakhtiar; Khairuddin Khairuddin; Reki Yelis; oktarifaldi oktarifaldi; Lucy Pratama Putri; Suci Nanda Sari (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
The problem in this study is the low ability of the object of control of kindergarten students in Padang Panjang City of Trustees. The ability of the control object is influenced by many factors, including the learning strategy used on the ability of object control students in TK Padang Panjang. This research uses quasy experiment design. The population in this study were all kindergarten students in Padang Panjang, amounting to 80 people. The sampling technique is done by total sampling. Control object capability data is obtained by giving the TGMD-2 test. Data were analyzed using a two-way variant analysis (ANAVA) technique with a 2x2 factorial design. The results of research and data analysis show that: 1) There is a difference in the ability of basic movement skills between groups of children who are given a direct feedback of indirect feedback with a value of Q 4.19> Qtable 2.95). 2) There is a difference high coordination and a child who has a low coordination Q count 5.91> Qtable 2.95. 3) There is an interaction between feedback with the level of coordination towards the mastery of basic child movement skills which is shown with a value of 0.000 <0.05. 4) There is a difference in the ability of basic child movement skills between groups who have a high coordination with direct feedback with the calculation of the value of Q count 12.03> Q table 3.15. 5) There is a difference in the ability of basic movement skills of children between groups of children who have a low coordination given indirect feedback with children who are given direct feedback with a Q count value of 4.03> Qtable 3.15